Physical and chemical properties of the urban soil in the San Juan de Aragon Park, Mexico City - Saavedra-Romero, Luz de Lourdes; Alvarado-Rosales, Dionicio; Martínez-Trinidad, Tomás; Hernández-de la Rosa, Patricia (REVISTA TERRA LATINOAMERICANA, 2020)
In view of the lack of studies on urban soils in Mexico, this paper evaluated eight physical and chemical properties used by the Soil Condition Indicator of the FIA (Forest Inventory and Analysis National Program, United States), to determine the quality of the soils and its role in the developmentof tree species present in the San Juan de Aragon Park. The properties evaluated and analyzed in horizontal and vertical terms were: pH, electrical conductivity, salt content, texture, bulk density, and percentages of organic matter, organic carbon and porous space. 96 soil samples were collected over 28 sampling sites of 0.1 ha, at three depths, 0-5, 5-10 and 10-15 cm. The average soil pH was 7.2; electrical conductivity, 0.51 dS m-1; bulk density, 1.02 g cm-3; porous space, 61.84%; total dissolved salts, 327.20 mg L-1; organic matter, 3.6% and organic carbon, 2.63%, as well as a frank textural class. The soils of the study area presented vertical variability for apparent density, porous space, organic matter, organic carbon, electrical conductivity, and soluble salts, and were relatively homogeneous horizontally. Except for organic matter, the rest of the properties presented acceptable values for good development of the tree species present. The measurement of the evaluated properties, allowed to obtain a real panorama about the ability of this urban land to function, which is adequate to support the development of woody species.